2015
DOI: 10.1001/jamaoto.2014.2895
|View full text |Cite
|
Sign up to set email alerts
|

Tumors of the Pediatric Maxillofacial Skeleton

Abstract: Pediatric jaw tumors are rare lesions most commonly presenting with a swelling or mass. Patients can be asymptomatic with the lesion identified on routine imaging. Certain clinical features such as age, location of tumor, and presence or absence of bone and soft tissue can narrow the differential diagnosis and identify tumors that may be malignant. Incisional biopsy is an important first step. A majority of jaw tumors are benign but require surgical intervention for eradication of disease. Multiple procedures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…The radical approach includes surgical resection with a clear margin of uninvolved bone and soft tissue. 13 Solid and multicystic tumors are aggressive with recurrence rates of 75-90% after conservative management. 1,14 Radical surgical treatment is therefore advocated and has been shown to improve outcomes.…”
Section: Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…The radical approach includes surgical resection with a clear margin of uninvolved bone and soft tissue. 13 Solid and multicystic tumors are aggressive with recurrence rates of 75-90% after conservative management. 1,14 Radical surgical treatment is therefore advocated and has been shown to improve outcomes.…”
Section: Managementmentioning
confidence: 99%
“…1,14 Radical surgical treatment is therefore advocated and has been shown to improve outcomes. 13,15 In their 2006 paper, Carl and Marx advocated radical surgical resection with a 1 to 1.5cm margin after finding that the tumors extended 2 to 8mm beyond their radiographic demarcation on histopathological evaluation. Using this approach, a review of 82 ameloblastoma resections showed no recurrence after 5 years.…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations